2016
DOI: 10.14419/ijpt.v4i1.5975
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of acute poisoning in teaching hospital, northwest Ethiopia

Abstract: Background: Acute poisoning is considered a major health problem worldwide and is a frequent cause of hospital admission. It is estimated that poisons are responsible for more than 1 million illnesses worldwide annually. Objective: To evaluate retrospectively the pattern of acute poisoning in teaching hospital, northwest Ethiopia. Materials and methods:This was an observational, retrospective study. The study population includes all patients who visiting Gondar teaching hospital emergency room who were diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
6
6
0
Order By: Relevance
“…The number and percentage of poisoning is equal in age groups 71-80 and 91-100 years (0.9%) while no case was noted in age group 81-9-years (0%). The findings are in line with the studies done in past by Pawaret al 13 31 which showed suicide being the commonest manner followed by accident. Study done by Sharma et al 33 showed that most common manner of poisoning was suicidal (50.89%) followed by accidental (44.57%) and lowest was homicidal (00.33%).…”
Section: Observations and Resultssupporting
confidence: 93%
“…The number and percentage of poisoning is equal in age groups 71-80 and 91-100 years (0.9%) while no case was noted in age group 81-9-years (0%). The findings are in line with the studies done in past by Pawaret al 13 31 which showed suicide being the commonest manner followed by accident. Study done by Sharma et al 33 showed that most common manner of poisoning was suicidal (50.89%) followed by accidental (44.57%) and lowest was homicidal (00.33%).…”
Section: Observations and Resultssupporting
confidence: 93%
“…The most common route of exposure for the acute poisoning in 508 (85.8%) of the women was through oral route. This finding was similar to a previous retrospective study carried out in north‐west Ethiopia , which was 83.6%.…”
Section: Discussionsupporting
confidence: 92%
“…The mean arrival time to the emergency department was 4.14 h, and the duration of hospital stay in most of the cases (483/81.6%) was 24 h or less. The mean arrival time and duration of hospital stay were closely similar to the acute poisoning study of both sexes in the Gonder teaching hospital, Ethiopia .…”
Section: Discussionsupporting
confidence: 70%
“…Reported in one study, places of poisoning were identified to be outside of home 8 (6.3%), Unknown25 (19.5%) [ 17 ]. Two studies reported that spring (32.2%) and July (14.6%) were the predominant season and month, respectively, associated with higher occurrence of acute poisoning [ 1 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…of cases reviewed Circumstance (%) Frequent manifestations at presentation Treatment (pre-hospital and /or hospital)/further prevention Reasons for poisoning outcomes I UI UD Bacha 2015 [ 17 ] Multi-center Prescribed drugs (29.7%) Hydrocarbon (18.3%) OPP (14.8%) Sodium hypochlorite (12.5%) Alcohol (8.7%) 128 15.5 77.5 7.0 Hypothermia (34.4%) Tachycardia (17.2%) Fever (7.0%) Atropine (6.3%) for OPP, Gastric lavage (18%), Antacids (53.3%) for detergent poisoning, Milk (83.3%), Induced vomiting (1.6%) CFR = 0 TAHI = 15.5 h (median) Teklemariam 2016 [ 18 ] JUSH HCA (41.7%), OPP (27.2%) Drugs (12.6%) Oral ingestion (97.1%) 103 50.5 . 27.2 22.3 Diarrhea and vomiting (49.5%), altered consciousness (16.5%)and epigastric pain (13.6%) GI decontamination (78.6%), Specific antidotes (12.6%), Other managements (8.7%) Psychiatric referral 8.7% and specific education 40.8% Quarrel (family, marital) (75.9%), psychiatric problem (14.8%) and Substance abuse (9.3%) LOS = 17.7 days(median) CFR = 5.8% TAHI = 30`-1 h Adinew 2017 [ 14 ] UOG hospital OPP (38.46%) Oral ingestion (88.9%) Inhalation 2.2% unknown 8.9% 90 90 Loss of consciousness (22.2%) Decontamination methods such as gastric lavage and activated charcoal (45.6%) and atropine (36.7%) for OPP Family (45.8%) andMarital (16.9%) disharmony, Unsuccessful love affairs (7.3%), Domestic violence (pregnant after raped) 4 (4.8%), Mental disorder 7 (8.4), Being RVI 4 (4.8%), Conflicts in work area (4.8%), Financial problem (4.8%) CFR = 0 LOS = 0.74 (mean) TAHI = 13`-1 day Adinew 2016 [ 20 ] UOG hospital OPP (38.2%), sodium hypochlorite (41.63%), drug (6.9%) and CO (6.0%) Oral ingestion (83.6%), inhalation (6.4%) 233 57.5 23.2 19.3...…”
Section: Resultsmentioning
confidence: 99%